Impact of Geometry on Magnetic Textures in Fege Nanowires: Fractional Skyrmion-Vortex States, Twisted Skyrmions, and Helical States - Escrig-Murua, J; Saavedra-Díaz, E (Elsevier Ltd, 2025)
We investigate the geometric phase space of magnetization states in isolated FeGe nanowires under an external magnetic field tilted 1°from the z-axis. Through micromagnetic simulations, we map the magnetic states as a function of aspect ratio (δ) and nanowire diameter (D), identifying three distinct regions: fractional skyrmion-vortex state, twisted skyrmionic, and helical states. These transitions are dictated by the nanowire s geometry, with increasing diameters leading to a progression from fractional skyrmion-vortex states to twisted skyrmions and finally to helical configurations, driven by the interplay of exchange interactions, anisotropy, and Dzyaloshinskii–Moriya effects. 3D visualizations of magnetization configurations illustrate these states. The coercivity and normalized remanence of FeGe nanowires depend on both D and δ, with smaller diameters exhibiting stronger shape anisotropy. Hysteresis curves reveal significant variations in topological charge and coercivity across different δ and D values, with pronounced spin rotations and phase transitions observed during the magnetization reversal. These findings underscore the critical role of nanowire geometry in governing the stability and dynamics of topological magnetic textures, offering valuable insights for spintronic applications that require precisely tailored magnetic states for efficient information storage and processing. © 2025 Elsevier B.V.